STAR syndrome-associated CDK10/Cyclin M regulates actin network architecture and ciliogenesis. Issue 5 (3rd March 2016) - Guen, Vincent J.; Gamble, Carly; Perez, Dahlia E.; Bourassa, Sylvie; Zappel, Hildegard; Gärtner, Jutta; Lees, Jacqueline A.; Colas, Pierre
ABSTRACT: CDK10/CycM is a protein kinase deficient in STAR (toe Syndactyly, Telecanthus and Anogenital and Renal malformations) syndrome, which results from mutations in the X-linked FAM58A gene encoding Cyclin M. The biological functions of CDK10/CycM and etiology of STAR syndrome are poorly understood. Here, we report that deficiency of CDK10/Cyclin M promotes assembly and elongation of primary cilia. We establish that this reflects a key role for CDK10/Cyclin M in regulation of actin network organization, which is known to govern ciliogenesis. In an unbiased screen, we identified the RhoA-associated kinase PKN2 as a CDK10/CycM phosphorylation substrate. We establish that PKN2 is a bone fide regulator of ciliogenesis, acting in a similar manner to CDK10/CycM. We discovered that CDK10/Cyclin M binds and phosphorylates PKN2 on threonines 121 and 124, within PKN2′s core RhoA-binding domain. Furthermore, we demonstrate that deficiencies in CDK10/CycM or PKN2, or expression of a non-phosphorylatable version of PKN2, destabilize both the RhoA protein and the actin network architecture. Importantly, we established that ectopic expression of RhoA is sufficient to override the induction of ciliogenesis resulting from CDK10/CycM knockdown, indicating that RhoA regulation is critical for CDK10/CycM's negative effect on ciliogenesis. Finally, we show that kidney sections from a STAR patient display dilated renal tubules and abnormal, elongated cilia. Altogether, these results reveal CDK10/CycM as a key regulator of actin dynamics and a suppressor of ciliogenesis through phosphorylation of PKN2 and promotion of RhoA signaling. Moreover, they suggest that STAR syndrome is a ciliopathy.